2011
DOI: 10.1016/j.jconrel.2011.08.029
|View full text |Cite
|
Sign up to set email alerts
|

PEG-stabilized lipid disks as carriers for amphiphilic antimicrobial peptides

Abstract: This is an accepted version of a paper published in Journal of Controlled Release. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the published paper: Zetterberg, M., Reijmar, K., Pränting, M., Engström, Å., Andersson, D. et al. (2011) AbstractAntimicrobial peptides hold potential as a possible alternative, or complement, to conventional antibiotics but new, safe and efficient means are needed for formulation and administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 16 publications
6
71
0
Order By: Relevance
“…The PEG-stabilized disks were found to be capable of releasing the bound melittin molecules, which resulted in the disruption of the 5(6)-carboxyfluorescein loaded POPC/1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoglycerol (POPG) (90:10 mol%) liposomes [153]. Importantly, the formulation of the cationic AMP in the disks effectively mediated protection against trypsin degradation, which was attributed to steric hindrance to the approach of the protease caused by PEG chains located at the disk rim.…”
Section: Delivery Of Membrane-active Ampsmentioning
confidence: 99%
“…The PEG-stabilized disks were found to be capable of releasing the bound melittin molecules, which resulted in the disruption of the 5(6)-carboxyfluorescein loaded POPC/1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoglycerol (POPG) (90:10 mol%) liposomes [153]. Importantly, the formulation of the cationic AMP in the disks effectively mediated protection against trypsin degradation, which was attributed to steric hindrance to the approach of the protease caused by PEG chains located at the disk rim.…”
Section: Delivery Of Membrane-active Ampsmentioning
confidence: 99%
“…As both faces of the lipid bilayer are exposed to the surrounding media, lipodisks are ideal systems for interaction studies. Recent research has also shown that they are potentially useful as drug carriers 24 . Following adequate protocols, lipodisks can be immobilized on a variety of substrates, including quartz crystal microbalance (QCM) 5 and surface plasmon resonance (SPR) 25 sensors , as well as on chromatographic media 5,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…These peptides are of great interest in pharmaceutical applications, as some of them have antimicrobial activity. It has been shown that incorporation of these peptides into lipodisks is an excellent way of achieving a sustained release of the compound as well as to protect the peptide from enzymatic degradation 24 . The method described in this report is able to quantify the amount of peptide that can be carried by a lipodisk, as well as the physicochemical parameters describing the peptide-lipodisk association.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we have already shown that PP-g-PEG patches have good soft tissue response, and the biocompatibility of the polymer is increased as more of a PEG side chain is added [14]. Many studies have reported that hydrophilic surfaces, such as PEGgrafted polymers, suppress protein adsorption and platelet adhesion [12,18,45]. These surface characteristics help this graft copolymer to reduce protein deposition that promotes pathogen adhesion and growth on device surfaces [31,35,36].…”
Section: Groups-catheter: Interaction Between Groups and Catheter Facmentioning
confidence: 99%